Modeling and analysis of the impact of information and communication technology on household consumption expenditure in different regions - Fan, Chaozhi; Law, Siong Hook; Ibrahim, Saifuzzaman; Naseem, N. A. M. (Hindawi, 2022)
Based on the panel data of cities and towns in China, by using the generalized estimation method of a dynamic panel, through the construction of regional household consumption expenditure evaluation models, optimize the impact evaluation algorithm of household consumption expenditure in different regions, standardize critic indicators, and build the impact modeling of household consumption expenditure in combination with relevant algorithms such as the Engel coefficient. Finally, it is verified by experiments that the impact model of ICT on household consumption expenditure in different regions has high practicability and fully meets the research requirements.